2011
DOI: 10.1038/emboj.2011.241
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of core histones reveals nucleosomal surfaces required for chromosome bi-orientation

Abstract: The attachment of sister kinetochores to microtubules from opposite spindle poles is essential for faithful chromosome segregation. Kinetochore assembly requires centromere‐specific nucleosomes containing the histone H3 variant CenH3. However, the functional roles of the canonical histones (H2A, H2B, H3, and H4) in chromosome segregation remain elusive. Using a library of histone point mutants in Saccharomyces cerevisiae, 24 histone residues that conferred sensitivity to the microtubule‐depolymerizing drugs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 69 publications
(145 reference statements)
1
37
0
Order By: Relevance
“…As described above, H2A.Z contributes to proper chromosome segregation in budding yeast (Krogan et al 2004;Measday et al 2005;Sopko et al 2006;Kawashima et al 2011), raising the possibility that, as in higher eukaryotes, H2A.Z contributes to the conformation of chromatin structure of centromeric regions. Our data show that the pericentric regions of budding yeast chromosomes 4 and 12 have aberrant chromatin structure when Ino80 or Ies6 is missing, and there is an increase in H2A.Z enrichment at these locations in ino80 and ies6 mutant strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described above, H2A.Z contributes to proper chromosome segregation in budding yeast (Krogan et al 2004;Measday et al 2005;Sopko et al 2006;Kawashima et al 2011), raising the possibility that, as in higher eukaryotes, H2A.Z contributes to the conformation of chromatin structure of centromeric regions. Our data show that the pericentric regions of budding yeast chromosomes 4 and 12 have aberrant chromatin structure when Ino80 or Ies6 is missing, and there is an increase in H2A.Z enrichment at these locations in ino80 and ies6 mutant strains.…”
Section: Discussionmentioning
confidence: 99%
“…We first tested the ability of the mutant strains to survive in the presence of the microtubule-destabilizing drug benomyl and found that, similar to strains with defective centromere or kinetochore structure (Kawashima et al 2011;Storchova et al 2011), both ies6 and ino80 strains are hypersensitive compared with wild type (Fig. 5A).…”
Section: Ies6 and Ino80 Function To Promote Proper Chromosome Segregamentioning
confidence: 99%
See 1 more Smart Citation
“…Although many screens for histone mutations that affect genomic stability have been reported (Smith et al 1996;Hyland et al 2005;Matsubara et al 2007;Dai et al 2008;Sakamoto et al 2009;Kawashima et al 2011;Yu et al 2011), none have been specifically directed at measuring chromosome segregation frequencies or sensitivity to Ipl1/Aurora downregulation. While this work was in progress, Kawashima et al (2011) reported a systematic screen of all histone mutants for sensitivity to the microtubule-depolymerizing agents benomyl and thiabendazole. There was little overlap of mutants identified in their study with those identified here, with the exception of H3 G44A and H4 Y98A.…”
Section: Discussionmentioning
confidence: 99%
“…S3A). Thirtyeight phenotypic residues of H2B have been identified by previous screening of the histone-GLibrary (nonfused H2B point mutant library) (23)(24)(25). We individually mutated 3 (H2B-D71, -L109, or -K123) of 38 residues in the H2B-H2A and H2B-Htz1 fusions.…”
Section: Resultsmentioning
confidence: 99%